miR-196b-5p Regulates Colorectal Cancer Cell Migration and Metastases through Interaction with HOXB7 and GALNT5 - Stiegelbauer, Verena; Vychytilova-Faltejskova, Petra; Karbiener, Michael; Pehserl, Anna-Maria; Reicher, Andreas; Resel, Margit; Heitzer, Ellen; Ivan, Cristina; Bullock, Marc; Ling, Hui; Deutsch, Alexander; Wulf-Goldenberg, Annika; et al. (Clinical cancer research, 2017)
Purpose: miR-196b-5p has been previously implicated in malignant transformation; however, its role in colorectal cancer has not been fully explored. In this study, we examine the clinical and biological relevance of miR-196b-5p, and the molecular pathways regulated by miR-196b-5p in colorectal cancer.Experimental Design: miR-196b-5p expression was quantitated by qRT-PCR in 2 independent cohorts composed of 292 patients with colorectal cancer in total, to explore its biomarker potential. Transient and stable gain- and loss-of-function experiments were conducted in a panel of colorectal cancer cell lines and mice, to evaluate the impact of miR-196b-5p on proliferation, chemosensitivity, migration/invasion, and metastases formation in vitro and in vivo The molecular pathways influenced by miR-196b-5p were characterized using whole transcriptome profiling, in silico target prediction tools, luciferase interaction assays, and phenocopy/rescue gene knockdown experiments.Results: Low miR-196b-5p expression was significantly associated with metastases and poor outcomes in 2 independent colorectal cancer patient cohorts (P < 0.05, log-rank test). miR-196b-5p inhibition led to significantly increased colorectal cancer cell migration/invasion and metastases formation in mice, whereas ectopic overexpression showed the opposite phenotype. Molecular profiling and target confirmation identified an interaction between miR-196b-5p and HOXB7 and GALNT5, which in turn regulated colorectal cancer cell migration.Conclusions: The association of low levels of miR-196b-5p and poor prognosis in patients with colorectal cancer can be explained by its influence on cancer cell migration and metastases formation. miR-196b-5p has an impact on colorectal cancer progression pathways through direct interaction with genes involved in cancer cell migration. Clin Cancer Res; 23(17); 5255-66. ©2017 AACR.
Keywords: Gene Expression Regulation, Neoplastic; Disease-Free Survival; Neoplasm Metastasis; Male; MicroRNAs; kolorektální nádory; Cell Line, Tumor; Cell Proliferation; mikro RNA; Xenograft Model Antitumor Assays; regulace genové exprese u nádorů; Adult; N-Acetylgalactosaminyltransferases; Aged; dospělí; mužské pohlaví; senioři; Cell Movement; xenogenní modely - testy protinádorové aktivity; senioři nad 80 let; Animals; lidé; ženské pohlaví; Humans; zvířata; pohyb buněk; Aged, 80 and over; myši; proliferace buněk; Colorectal Neoplasms; polypeptid-N-acetylgalaktosaminyltransferasa; Homeodomain Proteins; nádorové buněčné linie; Mice; Female; metastázy nádorů; Polypeptide N-acetylgalactosaminyltransferase; lidé středního věku; homeodoménové proteiny; přežití bez známek nemoci; N-acetylgalaktosaminyltransferasy; Middle Aged